2011
DOI: 10.1016/j.bpj.2011.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Structured Functional Domains of Myelin Basic Protein: Cross Talk between Actin Polymerization and Ca2+-Dependent Calmodulin Interaction

Abstract: The 18.5-kDa myelin basic protein (MBP), the most abundant isoform in human adult myelin, is a multifunctional, intrinsically disordered protein that maintains compact assembly of the sheath. Solution NMR spectroscopy and a hydrophobic moment analysis of MBP's amino-acid sequence have previously revealed three regions with high propensity to form strongly amphipathic α-helices. These regions, located in the central, N- and C-terminal parts of the protein, have been shown to play a role in the interactions of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Separate CD experiments conducted on this peptide in aqueous conditions [23] (see also Figure S3), indicated that although the central α-helical structure is much less well defined, there could be some residual secondary structure present under these conditions. This result was consistent with solution NMR data obtained on the entire 18.5-kDa protein [27].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Separate CD experiments conducted on this peptide in aqueous conditions [23] (see also Figure S3), indicated that although the central α-helical structure is much less well defined, there could be some residual secondary structure present under these conditions. This result was consistent with solution NMR data obtained on the entire 18.5-kDa protein [27].…”
Section: Resultsmentioning
confidence: 99%
“…The central (P82-I90) segment that is contained within the α 2 -peptides used in this study is an unequivocal α-helical molecular recognition fragment (α-MoRF). This region is disordered in water, but becomes α-helical upon interaction with phospholipids and other surfactants, or in the presence of membrane-mimetic solvents such as TFE ([23], [27], [51], [54], and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations